The Growing Number of Cybersecurity Vulnerabilities Inside Healthcare Supply Chain - McBride, Maurice L. (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The healthcare supply chain is increasingly vulnerable to cybersecurity risks due to the integration of digital technology. The rise of digital records, telemedicine, and network connectivity has made it more susceptible to cyberattacks. The COVID-19 pandemic has further exacerbated this vulnerability, highlighting deficiencies in medical supplies, equipment, and services. The sector has implemented cybersecurity precautions, such as following HIPAA and GDPR, and collaborating with authorities and experts. However, the changing threat landscape necessitates continuous updates and changes. The study uses secondary data from the past three years to highlight the need for strong cybersecurity protocols to protect patient data, deliver services, and defend the supply chain from new threats. Future research should explore leveraging blockchain and AI-based cybersecurity, as well as strengthening government regulation, international cooperation, cybersecurity education, and patient empowerment.